Preventive measures of struck-by accidents at the construction site: Perspectives from construction personnel in Johor - Yap, Wan Heong; Abas, Nor Haslinda; Rahmat, Muhamad Hanafi; Mohammad, Hairuddin (2022)
Struck-by accidents are among the main contributor to fatality number in the Malaysian construction industry. From the standpoint of construction safety professionals, this study explores the main preventive measures for struck-by accidents at the construction site. The data for this study was gathered through the questionnaire distributed to construction site safety workers in Johor, Malaysia, and about 116 answered questionnaires were received. Data were analyzed using the Relative Importance Index (RII) and Spearman’s rank correlation. The main preventive measure factor identified was related to training. This study provides eye-opening findings in terms of the weak correlational relation between the views of safety personnel and the most effective preventive strategy. This research raises awareness of the problem, and more action should be made to lower the fatality rate in struck-by-object accidents.